Pulmonary lymphoid neogenesis in idiopathic pulmonary arterial hypertension - Perros, Frédéric; Dorfmüller, Peter; Montani, David; Hammad, Hamida; Waelput, Wim; Girerd, Barbara; Raymond, Nicolas; Mercier, Olaf; Mussot, Sacha; Cohen-Kaminsky, Sylvia; Humbert, Marc; Lambrecht, Bart N (American journal of respiratory and critical care medicine, 2012)
Patients with idiopathic pulmonary arterial hypertension (IPAH) present circulating autoantibodies against vascular wall components. Pathogenic antibodies may be generated in tertiary (ectopic) lymphoid tissues (tLTs). To assess the frequency of tLTs in IPAH lungs, as compared with control subjects and flow-induced PAH in patients with Eisenmenger syndrome, and to identify local mechanisms responsible for their formation, perpetuation, and function. tLT composition and structure were studied by multiple immunostainings. Cytokine/chemokine and growth factor expression was quantified by real-time polymerase chain reaction and localized by immunofluorescence. The systemic mark of pulmonary lymphoid neogenesis was investigated by flow cytometry analyses of circulating lymphocytes. As opposed to lungs from control subjects and patients with Eisenmenger syndrome, IPAH lungs contained perivascular tLTs, comprising B- and T-cell areas with high endothelial venules and dendritic cells. Lymphocyte survival factors, such as IL-7 and platelet-derived growth factor-A, were expressed in tLTs as well as the lymphorganogenic cytokines/chemokines, lymphotoxin-α/-β, CCL19, CCL20, CCL21, and CXCL13, which might explain the depletion of circulating CCR6(+) and CXCR5(+) lymphocytes. tLTs were connected with remodeled vessels via an ER-TR7(+) stromal network and supplied by lymphatic channels. The presence of germinal center centroblasts, follicular dendritic cells, activation-induced cytidine deaminase, and IL-21(+)PD1(+) follicular helper T cells in tLTs together with CD138(+) plasma cell accumulation around remodeled vessels in areas of immunoglobulin deposition argued for local immunoglobulin class switching and ongoing production. We highlight the main features of lymphoid neogenesis specifically in the lungs of patients with IPAH, providing new evidence of immunological mechanisms in this severe condition.